2020
DOI: 10.3390/polym12051096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rutile–TiO2 Nanoparticles on Accelerated Weathering Degradation of Poly(Lactic Acid)

Abstract: The effect of accelerated weathering on poly(lactic acid) (PLA) and a PLA nanocomposite with rutile titanium (IV) dioxide (rutile–TiO2) was investigated. The accelerated weathering test applied consecutive steps of ultraviolet (UV) (at 340 nm and 0.76 W m−2 irradiance) and moisture at 50 °C for 2000 h, following the ASTM D4329 standard. The morphology, chemical structure, molecular weight, crystallization, as well as mechanical and thermal properties were thoroughly studied. Samples were characterized after 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…The T g values did not change with increasing weathering time for the nanocomposite, while there was an increase in these values with increasing weathering time for neat PHBV. This suggests that the smaller crystallites, formed during UV-initiated degradation, restrained the chain movement so that higher temperatures were needed for the amorphous chains to become mobile [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T g values did not change with increasing weathering time for the nanocomposite, while there was an increase in these values with increasing weathering time for neat PHBV. This suggests that the smaller crystallites, formed during UV-initiated degradation, restrained the chain movement so that higher temperatures were needed for the amorphous chains to become mobile [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study reported that the photodegradation of poly(butylene succinate- co -butylene adipate) was not affected by the addition of rutile TiO 2 nanoparticles coated with a silicon–aluminum composite [ 60 ]. On the other hand, Antunes et al [ 71 ] demonstrated the effect of rutile TiO 2 nanoparticles on the accelerated weathering degradation of poly(lactic acid). The presence of TiO 2 nanoparticles not only improved the cold crystallization behavior of the PLA, acting as nucleating agents, but the nanoparticles also catalyzed the UV-initiated degradation of the PLA.…”
Section: Introductionmentioning
confidence: 99%
“…As will be seen later in the discussion of the DSC results, after 2000 h degradation there are almost no PCL crystals left in the sample, while a reasonable number of PLA crystals have formed, that are probably visible as coalesced PLA spheres in the SEM picture of PLA/PCL/2000 h. The samples also became more yellow (Figure 1) because of the formation of chromophore groups (e.g., carboxyl, carbonyl, ketone, aldehyde, hydroxyl, ester, etc.) and conjugated double bonds in the polymers by the photo‐oxidative reactions during the accelerated weathering exposure 29 …”
Section: Resultsmentioning
confidence: 99%
“…The infrared spectrum of PLA presents the characteristic bands of the neat polymer. Since it is exactly the same polymer we used in our previous research, 29 we are not going to repeat the description of the spectrum here. The FTIR spectrum of neat PCL shows the absorption bands corresponding to the C═O stretching vibration at 1720 cm −1 and the CH 2 stretching at 2944 and 2863 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation